Decoding the Triterpenoid Gymnemic Acid Biosynthetic Pathway in Gymnema Sylvestre - Preetha R., Archana; Davis G., Dicky John; Neelima M., Gowri; B. S., Chaitra; B., Kirankumar (Journal of Neonatal Surgery, 2025)
Gymnemic acid, a bioactive compound with potential medicinal properties, is synthesized by a complex enzymatic process known as the denovo biosynthetic pathway. This pathway involves a series of well-coordinated steps starting from acetyl Co A till the synthesis of gymnemic acid, each series of reaction is catalyzed by biochemical conversion involving 15 enzymes. The enzymes required to catalyze the conversion of cochalicic acid to acacic acid and acacic acid to gymnemic acid have not been reported previously. Hence, this study highlights the link missing in the complex biomolecular transformation leading to synthesis of gymnemic acid. This is the first report to identify these enzymes as acacic acid synthase and gymnemic acid synthase. Additionally, organized schematic representation of biosynthetic pathway was deduced.